Public finance and public policy - Gruber, Jonathan ([Place of publication not identified] Worth Publisher, 2013)
The dynamic public policy environment of the past few years required a thorough updating of most aspect of the book. All statistics, data-related tables and figures and applications have been updated completely to reflect the most recent available data.
Part I. Introduction and background -- Part II. Externalities and public goods -- Part III. Social insurance and redistribution -- Part IV. Taxation in theory and practice
Includes bibliographical references and index.
Keywords: FINANCE PUBLIC; TAXATION